2013
DOI: 10.1155/2013/891431
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Expert Driving Behavior in Real World and Simulator Contexts

Abstract: Computer games are increasingly used for purposes beyond mere entertainment, and current hi-tech simulators can provide quite, naturalistic contexts for purposes such as traffic education. One of the critical concerns in this area is the validity or transferability of acquired skills from a simulator to the real world context. In this paper, we present our work in which we compared driving in the real world with that in the simulator at two levels, that is, by using performance measures alone, and by combining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…As has been pointed out by for example Lineberry et al (2013), these are methodological issues that make comparative analysis of the effectiveness of transfer problematic. Although the issue of transfer between simulator training and real-world situations admittedly is a problematic one, the definition and use of performance measures also influences how and to what extent effects of transfer can be measured and ascertained (Ramberg and Karlgren 1998;Artman et al 2013;Ekanayake et al 2013). Still, as witnessed by the analysis conducted in this article, some issues do not only concern measures but also common ground and communication between different actors, communities and formal bodies.…”
Section: Discussionmentioning
confidence: 91%
“…As has been pointed out by for example Lineberry et al (2013), these are methodological issues that make comparative analysis of the effectiveness of transfer problematic. Although the issue of transfer between simulator training and real-world situations admittedly is a problematic one, the definition and use of performance measures also influences how and to what extent effects of transfer can be measured and ascertained (Ramberg and Karlgren 1998;Artman et al 2013;Ekanayake et al 2013). Still, as witnessed by the analysis conducted in this article, some issues do not only concern measures but also common ground and communication between different actors, communities and formal bodies.…”
Section: Discussionmentioning
confidence: 91%
“…Scale in KSS described as follows [18][19][20]: 1 = very alert, 3 = alert, 5 = neither alert nor sleepy, 7 = sleepy, but no problem to stay awake, 9 = very sleepy, great effort to stay awake, and even numbers (2, 4, 6, and 8) as an intermediate score between odd score.…”
Section: Icohs 2017mentioning
confidence: 99%
“…The studies reported that sleepiness level is relatively higher compares to real driving [16][17][18]. Imitation of driving workload by simulator indeed has some limitations ICOHS 2017 such as pressure on safety during driving is less than real driving that may impact on performance variation during experiment [19], but in many conditions applying driving simulator allowed a researcher to minimize the risks that may occur during experiments.…”
Section: Introductionmentioning
confidence: 99%
“…ADAPTIVE TACTICAL BEHAVIOUR PLANNER The proposed novel behaviour planner framework is motivated by how experienced human drivers plan their behaviours in different traffic situations [84], [85]. The framework introduces a novel approach to mimicking human behaviour planning perception-prediction-action by having a three module behaviour planning framework.…”
Section: Behaviour Plannersmentioning
confidence: 99%